Refined oil production from Patin catfish (Pangasianodon hypophthalmus) by-products - Shabanikakroodi, Samana; Christianus, Annie; Tan, Chin Ping; Che Man, Yaakob; Ehteshami, Fariborz (Iranian Fisheries Research Organization, 2015)
In this study, oil was extracted from the liver and visceral fat of Patin (Pangasianodon hypophthalmus) and refined. The yield of oil after refining was 49.98%. The major yield loss (34.20%) happened during the degumming procedure. Fatty acids found in the crude and refined oil were C12:0, C14:0, C14:1, C16:0, C16:1, C18:0, C18:1, C18:2, C18:3, C18:4, C20:0, C20:1, C20:4, C20:5, and C22:6. The dominant saturated, monounsaturated and polyunsaturated fatty acids were C16:0, C18:1 n-9, and C18:2 n-6, respectively. The total amounts of monounsaturated fatty acids did not change significantly during refining procedure (p>0.05), whereas the total amount of saturated and polyunsaturated fatty acids changed significantly (p<0.05). The n-3 to n-6 ratios of crude, degummed, neutralized, bleached, and deodorized oils were 1.11, 1.06, 1.05, 1.02, and 1.01, respectively.